Karakteristik Pendidik di Era Digital [Educator's Characteristics in the Digital Era] - Lusiana Idawati; Niko Sudibjo (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Pelita Harapan, 2022)
The impact of technological developments in the era of the industrial revolution 4.0 and society 5.0 also impacts the education sector, such as the opening of access to learning resources via the internet, technology-based learning models, the development of various digital learning applications, and others. On the other hand, technological developments also have a negative impact, especially on students, such as an increase in individualism and a shift in Indonesian values. Therefore, this study aims to analyze the characteristics of education in the digital era. The research was carried out through Focus Group Discussions (FGD) involving various stakeholders in the education sector, including expert staff from the Ministry of Education and Culture, practitioners of primary and secondary education, lecturers, students, and educational technology development companies. The study results found three major themes of educator characteristics that teachers need to have in the digital era, namely having soft skills, personal-professional skills, and understanding character education.